Sinetron Leads to Negotiation of Identity: Christian Identity and the Representation of Religion in Indonesian Popular Culture - Kristi, Kristi (Pascasarjana IAIN Pontianak, 2018)
Having Pancasila as its ideology, with its first pillar of Ketuhanan yang Maha Esa (the belief in one deity), Indonesia is neither based on a certain religion, nor giving a privilege to a certain religion. In the context of the resurgence of religion, Islam obviously becomes the only normative in everyday life, including in popular culture. This paper analyzes the way Indonesian Christians see the representation of religion in sinetron, the television soap opera tat is considered the predominant form of popular culture in Indonesia, and negotiate their identity as religious minority. The work is based on a research project conducted in Gereja Kristen Jawa (GKJ/Christian Church of Java) Gondokusuman in Yogyakarta. A random survey about sinetron titles watched by the embers of the congregation show that eight titles are popular. A more intensive questionnaire is distributed to the church council as the representation of Christians who are active in church activities. It is also intended to show the most-watched sinetron in 2017. From the survey, there are two most watched sinetron: “Tukang Ojek Pengkolan” (TOP/Motorcycle-taxi Driver on the Corner) and “Dunia Terbalik” (DT/Upside-down World). Eighteen people who watch both TOP and DT then were interviewed. Using the framework of first generation of reception study, the work finds that Christians’ reception on the representation of religion in sinetron can be categorized into three patterns: mirror of reality, watching for pleasure, and religion is necessary. Those three patterns show that Christians’ reception is in negotiation position.